Heterogeneous catalyst, the mehod for producing the same, and synthesis method of a single enantiomer of selective chiral compounds by using the same
A silica-supported catalyst with polyimine-based polymer and metal particles addresses the limitations of existing enantiomer-selective catalysts by enhancing selectivity and efficiency in chiral compound synthesis.
Patent Information
- Application Number
- KR1020230144967
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-26
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-10-26
AI Technical Summary
Existing enantiomer-selective heterogeneous catalysts exhibit limited performance and complex synthesis processes, necessitating the development of highly selective catalysts that can be used universally.
A heterogeneous catalyst comprising a silica support with metal particles and a polyimine-based polymer, such as polyethyleneimine, is developed, with specific particle size, dispersion, and carbon content, and a manufacturing process involving heat treatment and calcination steps to enhance selectivity.
The catalyst achieves high selectivity for enantiomers, reducing raw material consumption and reaction waste, and enabling efficient chiral compound synthesis.
Smart Images

Figure 112023118116108-PAT00010_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a heterogeneous catalyst for the production of selective enantiomers, a method for manufacturing the same, and a method for synthesizing selective chiral compounds using the same. Background Technology
[0003] Chiral compounds, which lack intramolecular symmetry, possess two enantiomers with identical compositions. These two enantiomers are mirror-symmetric, much like a person's left and right hands, but they cannot overlap through rotation. While the two enantiomers differ in their optical properties regarding how they polarize light, their physical and chemical properties are generally identical.
[0004] Chiral compounds are utilized as raw materials and intermediates in fine chemical industries such as pharmaceuticals, pesticides, cosmetics, and food. This is attributed to the fact that two enantiomers can exhibit different physiological activities within the body. Biomolecules, including DNA and proteins, possess monochirality, exhibiting only one directionality; consequently, the two enantiomers of chiral compounds can react differently depending on their chirality. For example, while one enantiomer may exhibit useful physiological activity, the other may be toxic or inactive.
[0005] When producing chiral compounds through general chemical processes, racemic compounds are produced in which two enantiomers with identical physical and chemical properties are mixed in a 1:1 ratio. Although chiral separation technology is utilized to separate racemic compounds as a post-processing step to produce a single enantiomer, this method has limitations in terms of excessive consumption of chemical raw materials and the discharge of reaction waste, as half of the enantiomers with opposite chirality are discarded after production. To solve the above problems, it is necessary to develop a method for producing chiral compounds using enantiomer-selective catalytic reactions that selectively produce one of the two enantiomers.
[0006] Enantiomer-selective heterogeneous catalysts have very high industrial utility as they minimize the consumption of chemical raw materials and the discharge of reaction waste, while facilitating product separation and enabling continuous process utilization. The first successful chiral catalytic reaction utilizing a heterogeneous catalyst was the asymmetric hydrogenation of α-keto esters performed by the Orito research team in Japan in 1979. In this catalytic reaction, Pt / Al2O3, which generally exhibits good activity for hydrogenation reactions, was used as a catalyst, and chirality was imparted to the heterogeneous catalyst by adsorbing cinchona alkaloids onto a platinum surface using them as chiral modifiers. The reactant, α-keto ester, forms a complex with the cinchona alkaloid chiral modifiers at the chiral active sites on the catalyst surface, and selectively generates enantiomers due to the steric hindrance generated during this process.
[0007] Cinchona alkaloids, which act as chiral modifiers, contain a chiral central carbon, enabling the imparting of chirality through steric hindrance during the complex formation process with α-keto ester reactants. Furthermore, prior research has confirmed that the quinoline ring portion of the cinchona alkaloid structure facilitates the smooth adsorption of the modifier onto the active metal surface of the catalyst, while the nitrogen atom of the quinuclidine portion forms hydrogen bonds with the carbonyl portion of the reactant to directly participate in the hydrogenation reaction. In addition, previous studies have revealed that chiral modifiers can contribute to an increase in reaction rate by creating chiral active sites on the catalyst surface while simultaneously reducing the activation energy of the hydrogenation reaction.
[0008] Enantiomer-selective catalytic reactions utilizing such heterogeneous catalysts possess high utility value and potential; however, due to the difficulty in controlling the active sites of heterogeneous catalysts, they exhibit somewhat limited performance compared to homogeneous catalysts. Although various studies have recently been attempted to improve the performance of heterogeneous chiral catalysts, many still show low catalytic performance or complex synthesis processes, thus necessitating the development of highly selective heterogeneous chiral catalysts that can be used universally. The problem to be solved
[0010] In one embodiment of the present invention, a heterogeneous catalyst with high selectivity for enantiomers, a method for manufacturing the same, and a method for synthesizing a selective chiral compound using the same are provided. means of solving the problem
[0012] A heterogeneous catalyst according to one embodiment of the present invention may comprise a silica support; and metal particles supported on the silica support; and a polyimine-based polymer may be located on the surface of the silica support, and the polyimine-based polymer may be polyethyleneimine.
[0013] The metal particles supported on the silica support may include one or more selected from platinum (Pt), cobalt (Co), nickel (Ni), gallium (Ga), palladium (Pd), ruthenium (Ru), rhodium (Rh), iridium (Ir), rhenium (Re), tungsten (W), vanadium (V), gold (Au), silver (Ag), or copper (Cu).
[0014] The dispersion of metal particles supported on the silica support may be 5.0% to 25.0%.
[0015] The average particle size (D50) of the metal particles supported on the silica support is 1.65 nm to 1.75 nm, and the size of the supported metal particles may be in the range of 1.0 nm to 2.5 nm.
[0016] The CO adsorption capacity of the above heterogeneous catalyst is 0.050 cm 3 / g to 0.290 cm 3 It can be / g.
[0017] Based on the total amount of metal particles supported on the silica support, the percentage of metal particles with a particle size of 2.0 nm to 2.5 nm may be in the range of 10% to 25%, and based on the total amount of metal particles supported on the silica support, the percentage of metal particles with a particle size of 1.0 nm to 1.5 nm may be in the range of 20% to 30%.
[0018] The carbon content may be in the range of 3.0 wt% to 5.5 wt% based on the total mass of the above heterogeneous catalyst.
[0019] When analyzing the above heterogeneous catalyst using X-ray photoelectron spectroscopy (XPS), the intensity ratio P2 / P1 value of the peak (P2) appearing between 71 to 73 eV to the peak (P1) appearing between 70 to 71 eV can be 1.21 to 4.00.
[0020] A method for preparing a heterogeneous catalyst according to another embodiment of the present invention may include the step of mixing and reacting a silica support with a polyimine-based polymer to obtain a modified silica support; and the step of mixing and reacting the modified silica support with a metal salt to obtain a catalyst, wherein 150 wt% to 250 wt% of the polyamine-based polymer may be mixed based on the mass of the silica support.
[0021] In the step of mixing and reacting the above silica support with a polyimine-based polymer to obtain a modified silica support, the polyimine-based polymer may be polyethyleneimine.
[0022] The step of obtaining a modified silica support by mixing and reacting the silica support and a polyimine-based polymer may include: a step of preparing a dispersion by dispersing the silica support in distilled water; a step of obtaining a mixture by mixing an aqueous solution of the polyimine-based polymer with the dispersion; and a step of heat-treating the mixture.
[0023] The step of obtaining a mixture by mixing a polyimine-based polymer into the dispersion above may involve stirring the mixture at a stirring speed of 400 rpm to 600 rpm.
[0024] The step of heat-treating the above mixture may include: a step of heating the above mixture to obtain a dried solid; and a step of calcining the dried solid to obtain a modified silica support.
[0025] The step of heating the above mixture to obtain a dried solid can be performed at a temperature of 90°C to 110°C for 10 to 14 hours.
[0026] The step of obtaining a modified silica support by calcining the above-mentioned dried solid can be performed at a temperature of 300°C to 400°C for 1 hour to 9 hours.
[0027] The step of obtaining a catalyst by mixing and reacting the modified silica support and the metal salt may include: a step of obtaining a metal salt solution by dispersing the metal salt in an organic solvent; a step of obtaining a mixed dispersion by adding the modified silica support to the metal salt solution; and a step of heat-treating the mixed dispersion.
[0028] The step of obtaining a mixed dispersion by adding the modified silica support to the metal salt solution can be performed by adding the modified silica support to the metal salt solution and then stirring for 10 to 14 hours at a stirring speed of 150 to 250 rpm.
[0029] The step of adding the modified silica support to the metal salt solution to obtain a mixed dispersion can be performed at a temperature in the range of 35°C to 55°C.
[0030] The step of heat-treating the above-mentioned mixed dispersion may include: a step of heating the above-mentioned mixed dispersion to evaporate the solvent; and a step of calcining the above-mentioned catalyst precursor to obtain a catalyst.
[0031] The step of heating the above mixed dispersion to evaporate the solvent can be performed at a temperature in the range of 70°C to 90°C.
[0032] The step of obtaining a catalyst by calcining the above catalyst precursor can be performed by calcining at a temperature in the range of 300°C to 400°C in a reducing atmosphere.
[0034] In another embodiment of the present invention, a method for synthesizing selective chiral is provided, comprising the steps of: mixing and pretreating the heterogeneous catalyst and the chiral modifier; and introducing an organic solution in which a chiral raw material is dissolved into the pretreated heterogeneous catalyst to synthesize the selective chiral.
[0035] The chiral modifier may include one or more selected from cinchonidine, cinchonine, quinine, or quinidine.
[0036] The step of mixing and pretreating the heterogeneous catalyst and the chiral modifier may include: a step of heat-treating the heterogeneous catalyst in a reducing atmosphere to obtain a reduced heterogeneous catalyst; a step of dispersing the reduced heterogeneous catalyst in an organic solvent and then mixing it with a chiral modifier to obtain a mixture of the heterogeneous catalyst and the chiral modifier; and a step of supplying hydrogen gas to the mixture of the heterogeneous catalyst and the chiral modifier to form a hydrogen atmosphere.
[0037] The method may further include the step of forming a hydrogen atmosphere by supplying hydrogen gas to the mixture of the heterogeneous catalyst and the chiral reformer, and then supplying hydrogen gas to pressurize it to a range of 0.5 MPa to 5.0 MPa.
[0038] In the step of mixing and pretreating the above heterogeneous catalyst and chiral modifier, the above heterogeneous catalyst is regenerated and used at least 10 times.
[0039] The above selective chiral is one class of chirals derived from a compound represented by the following chemical formula 1, and its selectivity may be 60% or more.
[0040] [Chemical Formula 1]
[0041]
[0042] (In Formula 1, R1 and R2 each independently comprise an unsubstituted or substituted alkyl group; an unsubstituted or substituted aryl group; and a halogen group.) Effects of the invention
[0044] A heterogeneous catalyst according to one embodiment of the present invention has the effect of high selectivity for enantiomers.
[0045] A method for manufacturing a heterogeneous catalyst according to one embodiment of the present invention can produce a catalyst with high selectivity for enantiomers. Brief explanation of the drawing
[0047] FIG. 1 schematically illustrates the manufacturing process flow of a heterogeneous catalyst according to one embodiment of the present invention. Figure 2 shows the TEM analysis results for heterogeneous catalysts prepared according to Preparation Examples 1 to 5 and Comparative Preparation Example 1. Figure 3 shows the FT-IR analysis results for heterogeneous catalysts prepared according to Preparation Examples 1 to 5 and Comparative Preparation Example 1. Figure 4 shows the XPS analysis results for heterogeneous catalysts prepared according to Preparation Examples 1 to 5 and Comparative Preparation Example 1. Figure 5 shows the TEM-EDS mapping results for the heterogeneous catalyst prepared according to Preparation Example 3. Figure 6 shows the experimental results of selective chiral synthesis according to the regeneration cycle of a heterogeneous catalyst prepared according to Preparation Example 3. Figure 7 shows the experimental results of selective chiral synthesis according to reaction pressure. Specific details for implementing the invention
[0048] Terms such as first, second, and third are used to describe various parts, components, regions, layers, and / or sections, but are not limited thereto. These terms are used solely to distinguish one part, component, region, layer, or section from another part, component, region, layer, or section. Accordingly, the first part, component, region, layer, or section described below may be referred to as the second part, component, region, layer, or section without departing from the scope of the present invention.
[0049] The technical terms used herein are for the reference of specific embodiments only and are not intended to limit the invention. The singular forms used herein include plural forms unless phrases clearly indicate otherwise. As used in the specification, the meaning of "comprising" specifies certain characteristics, areas, integers, steps, actions, elements, and / or components, and does not exclude the presence or addition of other characteristics, areas, integers, steps, actions, elements, and / or components.
[0050] When it is stated that one part is "above" or "on" another part, it may be directly above or on the other part, or other parts may be involved in between. In contrast, when it is stated that one part is "directly above" another part, no other parts are interposed in between.
[0051] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the same meaning as generally understood by those skilled in the art to which this invention pertains. Terms defined in commonly used dictionaries are further interpreted to have meanings consistent with relevant technical literature and the present disclosure, and are not interpreted in an ideal or highly formal sense unless otherwise defined.
[0052] Also, unless otherwise specified, % means wt%, and 1 ppm is 0.0001 wt%.
[0053] In this specification, the term “combination(s) of these” described in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including any one or more selected from the group consisting of said components.
[0054] Hereinafter, embodiments of the present invention are described in detail so that those skilled in the art can easily implement the invention. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0056] 1. Method for manufacturing heterogeneous catalysts
[0057] One embodiment of the present invention provides a method for manufacturing a heterogeneous catalyst.
[0058] Figure 1 schematically illustrates the manufacturing process flow of a heterogeneous catalyst according to one embodiment of the present invention.
[0059] Referring to FIG. 1, a method for manufacturing a heterogeneous catalyst according to one embodiment of the present invention may include the step of obtaining a modified silica support by mixing and reacting a silica support with a polyimine-based polymer; and the step of obtaining a catalyst by mixing and reacting the modified silica support with a metal salt.
[0060] The step of obtaining a modified silica support by mixing and reacting the silica support and a polyimine-based polymer may include: a step of preparing a dispersion by dispersing the silica support in distilled water; a step of obtaining a mixture by mixing the polyimine-based polymer into the dispersion; and a step of heat-treating the mixture.
[0061] The step of preparing a dispersion by dispersing the above silica (SiO2) support in distilled water may involve mixing 0.5g to 1.5g of the silica support, i.e., silica, into 1mL of distilled water, specifically 0.8g to 1.9g, and more specifically 0.9g to 1.1g. When mixed within the above range, the silica can be uniformly dispersed in the distilled water without clumping, and unnecessary energy consumption used to evaporate excess distilled water during the process of manufacturing the subsequent modified silica support can be prevented.
[0062] In the step of obtaining a mixture by mixing a polyimine-based polymer with the above dispersion, the polyimine-based polymer may be added to the dispersion and distilled water may be added simultaneously. At this time, 1 mL of distilled water may be added per 1 g of the polyimine-based polymer so that the polyimine-based polymer is uniformly dispersed within the mixture.
[0063] Meanwhile, 150 wt% to 250 wt% of a polyamine-based polymer can be mixed based on the mass of the silica support. The polyamine-based polymer may be polyethyleneimine (PEI), specifically having a weight-average molecular weight of about 25,000 g / mol. When PEI with the above molecular weight is applied, the surface of the active metal can be exposed during the subsequent heat treatment process, and the activity of the finally obtained heterogeneous catalyst can be improved.
[0064] By mixing the above polyamine-based polymer within the above range, a heterogeneous catalyst capable of producing the desired enantiomer with high selectivity in the present invention can be prepared.
[0065] In one embodiment of the present invention, after the addition of a polyimine-based polymer and distilled water to the dispersion, the mixture can be stirred at a stirring speed of 400 rpm to 600 rpm for 30 minutes or more, and specifically, for 30 minutes to 2 hours.
[0066] The step of heat-treating the above mixture may include: a step of heating the above mixture to obtain a dried solid; and a step of calcining the dried solid to obtain a modified silica support.
[0067] The step of heating the above mixture to obtain a dried solid can be performed at a temperature of 90°C to 110°C for 10 to 14 hours, and the step of calcining the dried solid to obtain a modified silica support can be performed at a temperature of 300°C to 400°C for 1 to 9 hours, specifically for 1 to 8 hours.
[0068] When heat-treated at the above temperature and time, a heterogeneous catalyst capable of producing enantiomers with high selectivity can be prepared.
[0069] The step of obtaining a catalyst by mixing and reacting the modified silica support and the metal salt may include: a step of obtaining a metal salt solution by dispersing the metal salt in an organic solvent; a step of obtaining a mixed dispersion by adding the modified silica support to the metal salt solution; and a step of heat-treating the mixed dispersion.
[0070] The step of obtaining a metal salt solution by dispersing the metal salt in an organic solvent may involve dissolving the metal salt by introducing it into an organic solvent, and the metal salt may be a metal salt comprising one or more selected from platinum (Pt), cobalt (Co), nickel (Ni), and gallium (Ga).
[0071] The step of obtaining a mixed dispersion by adding the modified silica support to the metal salt solution can be performed by adding the modified silica support to the metal salt solution and then stirring for 10 to 14 hours at a stirring speed of 150 to 250 rpm while maintaining a temperature in the range of 35°C to 55°C.
[0072] The step of heat-treating the above-mentioned mixed dispersion may include: a step of heating the above-mentioned mixed dispersion to evaporate the solvent to obtain a catalyst precursor; and a step of calcining the above-mentioned catalyst precursor to obtain a catalyst.
[0073] The step of obtaining a catalyst precursor by heating the above-mentioned mixed dispersion to evaporate the solvent is, specifically, a step of obtaining a catalyst precursor by evaporating the solvent in the above-mentioned gold salt solution, and can be heated at a temperature in the range of 70°C to 90°C for 10 hours or more, specifically for 10 to 14 hours.
[0074] The step of obtaining a catalyst by calcining the above catalyst precursor can be performed by calcining for at least one hour while maintaining a temperature in the range of 300°C to 400°C in a reducing atmosphere.
[0075] By heat treating under the above conditions, a heterogeneous catalyst capable of producing the enantiomers intended in the present invention with high selectivity can be prepared.
[0077] 2. Heterogeneous catalyst
[0078] A heterogeneous catalyst according to another embodiment of the present invention may comprise a silica support; and metal particles supported on the silica support; and a polyimine-based polymer may be located on the surface of the silica support.
[0079] The above polyamine-based polymer may be polyethyleneimine (PEI), specifically having a weight average molecular weight of about 25,000 g / mol, and is not particularly limited as long as it can produce the heterogeneous catalyst intended in the present invention.
[0080] The metal particles may include one or more selected from platinum (Pt), cobalt (Co), nickel (Ni), gallium (Ga), palladium (Pd), ruthenium (Ru), rhodium (Rh), iridium (Ir), rhenium (Re), tungsten (W), vanadium (V), gold (Au), silver (Ag), or copper (Cu), and specifically may be platinum (Pt).
[0081] The particle size of the metal particles may be 1.0 nm to 2.5 nm, and the average particle size (D50) may be 1.65 nm to 1.75 nm.
[0082] Meanwhile, based on the total quantity (number) of the metal particles, the quantity percentage of metal particles with a particle size of 2.0 nm to 2.5 nm may be 10% to 25%, and the quantity percentage of metal particles with a particle size of 1.0 nm to 1.5 nm may be 20% to 30%.
[0083] In the present invention, the metal particle size is the size of the metal particles observed in the TEM image, and the average particle size is the value calculated by averaging 80 to 120 metal particles located consecutively on the TEM image.
[0084] The dispersion of metal particles supported on a silica support of the heterogeneous catalyst of the present invention may be 2.0% to 21.0%, specifically 5.0% to 21.0%, and more specifically 7.0% to 21.0%.
[0085] In the present invention, the degree of dispersion of metal particles can be expressed as the weight percentage of metal particles exposed on the surface of the silica support relative to the total weight of metal particles supported on the silica support.
[0086] In the present invention, the degree of dispersion refers to the ratio of surface-exposed metal particles to actual supported metal particles, which can be measured through CO gas adsorption, and the metal particle size and degree of dispersion values can be derived through the volume of adsorbed CO gas by utilizing the property that CO gas is adsorbed in a 1:1 ratio per metal atom exposed on the surface.
[0087] (1)
[0088] Here
[0089] : Dispersion of metal particles
[0090] : Stoichiometry factor
[0091] : atomic weight of metal (195.084 for Pt)
[0092] Vchem : Amount of CO gas adsorbed on exposed platinum
[0093] am.
[0094] In other words, a lower degree of dispersion and larger particle size of the metal particles mean that fewer metal particles are exposed to CO gas, which implies that the catalyst surface is modified and masked by organic matter (PEI).
[0095] The metal particle size (d) can be calculated in the following way.
[0096] (2)
[0097] In the above equation (2), Am can be calculated using the following equation (3).
[0098] (3)
[0099] In the above equation (3), C can be calculated from the following equation (4).
[0100] = (4)
[0101] In the above equations (3) and (4), α is the number of metal particles, ρ is the radius of the metal particles, and ρ is the density of the metal particles.
[0103] The CO adsorption capacity of the heterogeneous catalyst of the present invention is 0.050 cm 3 / g to 0.290 cm 3 It can be / g, specifically 0.100 cm 3 / g to 0.290 cm 3 It can be / g.
[0104] Based on the total mass of the above heterogeneous catalyst, the carbon content may be 0.9% to 6.0 wt%, and specifically 0.9% to 5.5 wt%.
[0105] Based on the total mass of the above heterogeneous catalyst, the nitrogen content may be 1.0 wt% to 3.0 wt%, and specifically 1.4 wt% to 1.8 wt% or 2.5 wt% to 3.0 wt%.
[0106] Meanwhile, the heterogeneous catalyst according to the present invention exhibits Pt between 73 and 75 eV during X-ray photoelectron spectroscopy (XPS) analysis. x+ The peak (P3) of Pt appearing between 71 and 73 eV 2+ The peak (P2) or Pt appearing between 70 and 71 eV 0 A peak (P1) can be observed.
[0107] In the XPS analysis graph, the above Pt 0 Peak (P1), Pt 2+ Peak (P2) and Pt x+ This is the result obtained by quantifying all peaks (P3), and Pt 2+ and Pt x+ The ratio is the result of calculating the fraction of electron-deficient Pt out of the total Pt for each sample.
[0108] The P2 / P1 value, which is the ratio of the intensity of peak (P2) to the intensity of peak (P1), may be greater than 1.21, specifically in the range of 1.21 to 4.00, and more specifically in the range of 1.24 to 3.60.
[0109] Meanwhile, in the XPS analysis results, Pt 2+ and Pt x+ The percentage of may be 55.0% or more, specifically between 55.0% and 85.0%.
[0111] 2. Selective chiral synthesis method.
[0112] A method for synthesizing selective chiral according to another embodiment of the present invention may include the step of mixing and pretreating the heterogeneous catalyst and the chiral modifier; and the step of synthesizing selective chiral by introducing an organic solution in which a chiral raw material is dissolved into the pretreated heterogeneous catalyst.
[0113] Meanwhile, the above heterogeneous catalyst has been explained in detail above, so it will be omitted here.
[0114] In the present invention, the chiral modifier may include one or more selected from cinchonidine, cinchonine, quinine, or quinidine.
[0115] The step of mixing and pretreating the heterogeneous catalyst and the chiral modifier may include: a step of heat-treating the heterogeneous catalyst in a reducing atmosphere to obtain a reduced heterogeneous catalyst; a step of dispersing the reduced heterogeneous catalyst in an organic solvent and then mixing it with a chiral modifier to obtain a mixture of the heterogeneous catalyst and the chiral modifier; and a step of supplying hydrogen gas to the mixture of the heterogeneous catalyst and the chiral modifier to form a hydrogen atmosphere.
[0116] The step of obtaining a reduced heterogeneous catalyst by heat-treating the above heterogeneous catalyst in a reducing atmosphere can be performed by loading the above heterogeneous catalyst into a furnace and reducing it in a reducing gas atmosphere while maintaining the temperature at 150°C to 250°C. Specifically, the above heterogeneous catalyst can be reduced while continuously flowing 5 vol.% hydrogen (H2) gas (balance gas is Ar).
[0117] The step of dispersing the above-mentioned reduced heterogeneous catalyst in an organic solvent and then mixing a chiral modifier to obtain a mixture of the heterogeneous catalyst and the chiral modifier may involve dispersing the chiral modifier in an organic solvent and then introducing it into the organic solvent in which the above-mentioned reduced heterogeneous catalyst is dispersed. At this time, continuous stirring may be performed using a stirring means. The inside of the reactor may be formed into a hydrogen atmosphere at atmospheric pressure while flowing hydrogen gas through the mixture of the heterogeneous catalyst and the chiral modifier. At this time, the hydrogen gas may be supplied for 5 minutes or more, and specifically, for 10 to 20 minutes.
[0118] A step of synthesizing selective chiral can be performed by forming an atmospheric pressure atmosphere by continuously flowing hydrogen gas under the above atmospheric pressure conditions, and then introducing an organic solution in which a chiral raw material is dissolved while maintaining the atmospheric pressure conditions.
[0119] Meanwhile, in the present invention, a step of reducing by continuously flowing hydrogen gas under the above atmospheric pressure conditions, and then pressurizing to a range of 0.5 MPa to 5.0 MPa, may be additionally performed, and a step of synthesizing selective chiral by introducing an organic solution in which a chiral raw material is dissolved while maintaining the above pressurization conditions may be performed.
[0120] In the present invention, in the step of mixing and pretreating the heterogeneous catalyst and the chiral modifier, the heterogeneous catalyst can be regenerated and used 10 or more times, specifically 10 to 100 times, more specifically 10 to 50 times.
[0121] In the present invention, the selective chiral produced is one type of chiral derived from a compound represented by the following chemical formula 1, and its selectivity may be 60% or more.
[0122] [Chemical Formula 1]
[0123]
[0124] (In Formula 1, R1 and R2 each independently comprise an unsubstituted or substituted alkyl group; an unsubstituted or substituted aryl group; and a halogen group.)
[0126] Preferred embodiments and comparative examples of the present invention are described below. However, the following examples are merely preferred embodiments of the present invention, and the present invention is not limited to the following examples.
[0128] <Preparation Example 1 of a Heterogeneous Catalyst>
[0129] 1 g of SiO2 was added to 6 mL of distilled water and uniformly dispersed. 2 g of polyethylenimine (PEI) was uniformly dispersed in 2 mL of distilled water and then added to the prepared SiO2 dispersion. Next, the mixture was stirred using a stirrer at a stirring speed of 500 rpm for 1 hour. After stirring was completed, the resulting white mixture was placed in an oven and dried for 12 hours while maintaining a temperature of 100°C. Subsequently, the mixture was calcined for 1 hour while maintaining a temperature of 350°C to synthesize PEI-modified SiO2, i.e., PEI-SiO2-1. (PEI:SiO2=2:1, 350°C, 1 hr)
[0130] A wet impregnation method was used to support platinum (Pt) nanoparticles using the above-prepared PEI-SiO2-1. Platinum(II) acetylacetonate corresponding to a Pt content of 1.2 wt% was dissolved in 20 mL of acetone, and then 500 mg of PEI-SiO2-1 was added to the solution and dispersed. The mixture was then stirred while maintaining a temperature of 40 ℃ until all the solvent evaporated. After all the solvent evaporated, the resulting solid was placed in an oven and dried for 12 hours while maintaining a temperature of 80 ℃. Subsequently, a heterogeneous Pt catalyst was prepared by heat treatment for 3 hours while maintaining a temperature of 350 ℃ in an argon (Ar) atmosphere.
[0131] <Preparation Example 2 of a Heterogeneous Catalyst>
[0132] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-2 (PEI:SiO2=2:1 350℃, 2 hr), was prepared by calcining for 2 hours while maintaining a temperature of 350 ℃.
[0134] <Preparation Example 3 of a Heterogeneous Catalyst>
[0135] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-3 (PEI:SiO2=2:1 350℃, 3 hr), was prepared by calcining at a temperature of 350 ℃ for 3 hours.
[0137] <Preparation Example 4 of a Heterogeneous Catalyst>
[0138] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-4 (PEI:SiO2=2:1 350℃, 4 hr), was prepared by calcining at a temperature of 350 ℃ for 4 hours.
[0140] <Preparation Example 5 of a Heterogeneous Catalyst>
[0141] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-5 (PEI:SiO2=2:1 350℃, 5 hr), was prepared by calcining for 5 hours while maintaining a temperature of 350 ℃.
[0143] <Preparation Example 6 of a Heterogeneous Catalyst>
[0144] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-6 (PEI:SiO2=2:1 350℃, 6 hr), was prepared by calcining at a temperature of 350 ℃ for 6 hours.
[0146] <Preparation Example 7 of a Heterogeneous Catalyst>
[0147] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-8 (PEI:SiO2=2:1 350℃, 8 hr), was prepared by calcining for 8 hours while maintaining a temperature of 350 ℃.
[0149] <Comparative Preparation Example 1 of Heterogeneous Catalysts>
[0150] A wet impregnation method was also used to support Pt nanoparticles using only SiO2 (Sigma Aldrich) as a support, without using PEI. Platinum(II) acetylacetonate corresponding to the target Pt content was dissolved in 20 mL of acetone, then 500 mg of SiO2 was added to the solution and dispersed. The mixture was then stirred while maintaining the temperature at 40 ℃ until all the solvent evaporated. After all the solvent had evaporated, the resulting solid was placed in an oven and dried for 12 hours while maintaining the temperature at 80 ℃. Subsequently, a heterogeneous Pt catalyst was prepared by heat treatment in an argon (Ar) atmosphere at a temperature of 350 ℃ for 3 hours.
[0152] <Comparative Preparation Example 2 of Heterogeneous Catalysts>
[0153] A heterogeneous catalyst was prepared using the same method as in Preparation Example 3, except that SiO2 modified with PEI, namely PEI-SiO2-3-250 (PEI:SiO2=2:1 250℃, 10 hr), was prepared by calcining for 3 hours while maintaining a temperature of 250 ℃.
[0155] <Comparative Preparation Example 3 of Heterogeneous Catalysts>
[0156] A heterogeneous catalyst was prepared using the same method as in Preparation Example 3, except that SiO2 modified with PEI, namely PEI-SiO2-5-250 (PEI:SiO2=2:1 250℃, 10 hr), was prepared by calcining for 5 hours while maintaining a temperature of 250 ℃.
[0158] <Comparative Preparation Example 4 of Heterogeneous Catalysts>
[0159] A heterogeneous catalyst was prepared using the same method as in Preparation Example 3, except that SiO2 modified with PEI, namely PEI-SiO2-7-250 (PEI:SiO2=2:1 250℃, 10 hr), was prepared by calcining for 7 hours while maintaining a temperature of 250 ℃.
[0161] <Comparative Preparation Example 5 of Heterogeneous Catalysts>
[0162] A heterogeneous catalyst was prepared using the same method as in Preparation Example 1, except that SiO2 modified with PEI, i.e., PEI-SiO2-10 (PEI:SiO2=2:1 350℃, 10 hr), was prepared by calcining for 10 hours while maintaining a temperature of 350 ℃.
[0164] (Evaluation Example 1: TEM (Transmission electron microscopy) analysis)
[0165] Transmission electron microscopy (TEM) analysis was performed on the heterogeneous catalysts prepared according to Preparation Examples 1 to 5 and Comparative Preparation Example 1, and the analysis results are shown in Fig. 2.
[0166] Referring to FIG. 2, it can be seen that platinum nanoparticles are evenly dispersed on the surface of a support modified with organic material within the heterogeneous catalysts prepared according to Preparation Examples 1 to 5 and Comparative Preparation Example 1.
[0167] Meanwhile, the diameters of 80 to 120 platinum nanoparticles observed in the TEM image were measured, and the particle size distribution is shown in Figure 1.
[0168] Referring to FIG. 2, it can be seen that the particle size of the heterogeneous catalyst prepared according to Preparation Examples 1 to 5 is 1.0 nm to 2.5 nm, the average particle size is 1.65 nm to 1.75 nm, and specifically 1.7 nm. In addition, based on the total number of metals supported on the silica support, it can be seen that the number of metals with a particle size of 2.0 nm to 2.5 nm is 10% to 25%, and the number of metals with a particle size of 1.0 nm to 1.5 nm is 20% to 30%.
[0169] It was confirmed that the particle size of the heterogeneous catalyst prepared according to Comparative Preparation Example 1 is 1.0 nm to 2.5 nm, the average particle size is 1.55 nm to 1.65 nm, and specifically 1.6 nm. In addition, based on the total number of metals supported on the silica support, it was confirmed that the number of metals with a particle size of 2.0 nm to 2.5 nm is less than 10%, and the number of metals with a particle size of 1.0 nm to 1.5 nm exceeds 30%.
[0171] (Evaluation Example 2: Analysis of Carbon Monoxide (CO) Chemiadsorption Characteristics)
[0172] To quantitatively analyze the amount of active sites exposed on the surface of platinum nanoparticles of the synthesized heterogeneous catalyst, the carbon monoxide (CO) chemisorption method was analyzed using the BELCAT-II instrument from MicrotracBEL.
[0173] The above analysis method is based on the principle that CO gas is not adsorbed onto the support SiO2 and PEI-SiO2-t but is adsorbed only onto platinum atoms exposed on the surface of the supported catalyst in a 1:1 ratio. Specifically, the control catalyst synthesized in Comparative Example 1 or about 30 mg of heterogeneous catalyst synthesized in Preparation Examples 1 to 5 and Comparative Preparation Examples 1 to 4 is placed into the instrument and reduced with hydrogen gas at 200°C for 2 hours. Afterward, the temperature is lowered to 50°C, and CO gas is injected in a pulsed manner to calculate the amount of CO gas chemically adsorbed onto the sample.
[0174] The CO adsorption amount and the dispersion and particle size of platinum calculated based on it are shown in Table 1 below.
[0175] catalyst CO adsorption capacity [cm² 3 / g-catalyst] Platinum particle dispersion [%] Platinum particle size calculated using CO adsorption [nm] Preparation Example 1 0.106 7.7 14.7 Preparation Example 2 0.195 14.2 8.0 Preparation Example 3 0.217 17.2 6.6 Preparation Example 4 0.217 17.1 6.4 Preparation Example 5 0.271 18.9 6.2 Preparation Example 6 0.279 18.7 6.0 Preparation Example 7 0.288 20.8 5.7 Comparative Manufacturing Example 1 0.557 46.7 2.0 Comparative Manufacturing Example 2 0.008 0.7 173.9 Comparative Manufacturing Example 3 0.009 1.0 169.8 Comparative Manufacturing Example 4 0.012 1.2 165.7 Comparative Manufacturing Example 5 0.294 21.5 5.3
[0176] Referring to Table 1 above, it was found that the platinum particle size calculated using CO adsorption decreases as the heat treatment time increases. This is believed to be due to the decrease in organic matter remaining on the surface of the platinum particles as the heat treatment time increases. Referring to the equations (2) to (4) described above for calculating the platinum particle size using CO adsorption, as the heat treatment time increases, the organic matter remaining on the surface of the platinum particles decreases, increasing the surface area capable of adsorbing CO, and thus the calculated platinum particle size is calculated as a small value.
[0177] Referring to Table 1 above, the surface of the catalysts modified with PEI according to Preparation Examples 1 to 7 has a CO2 adsorption amount of 0.106 cm³ 3 / g to 0.288 cm 3 / g, and the platinum particle dispersion was found to be 7.7% to 20.8%.
[0179] (Evaluation Example 3: FI-IR Analysis)
[0180] Analysis of residual organic matter present on the surface of the fabricated heterogeneous catalyst was performed using transmission infrared spectroscopy (FT-IR).
[0181] 0.1 mg of each catalyst synthesized in Comparative Preparation Example 1 and Preparation Examples 1 to 5 and 9.9 mg of KBr were mixed and milled into a fine powder form, then formed into a thin pellet, and the transmission spectrum obtained using an infrared spectrometer is shown in Fig. 3.
[0182] Referring to FIG. 3, in the case of the catalysts of Examples 1 to 5 using PEI as the surface modification process, peaks corresponding to the functional groups of PEI were observed, and through this, it can be confirmed that PEI remains on the surface of the catalyst.
[0184] (Evaluation Example 4: XPS Analysis)
[0185] The chemical state of the platinum element was analyzed by X-ray photoelectron spectroscopy (XPS) analysis of the Pt catalysts prepared in Comparative Example 1 and Examples 1 to 5. Before XPS analysis, each sample was reduced by hydrogen treatment at 200°C and then measured. The XPS analysis results for Pt 4f are shown in Table 2 and Figure 4 below.
[0186] Catalyst Species (P1)Pt 0 [70.7 eV] (P2)Pt 2+ [72.2 eV] (P3)Pt x+ (2 <x<4) [74.5 eV] Fraction of Pt 2+ and Pt x+ (%) Comparative Manufacturing Example 1 45.4 54.6 - 54.6 Preparation Example 1 28.1 61.4 10.5 71.9 Preparation Example 2 19.8 70.5 9.7 80.2 Preparation Example 3 22.3 69.5 8.2 77.7 Preparation Example 4 32.4 59.1 8.5 67.6 Preparation Example 5 40.7 50.8 8.5 59.3
[0187] Referring to Table 2 and Fig. 4 above, the graph in Fig. 4 contains information regarding the oxidation state of the platinum element for each catalyst. For the Pt-containing catalysts prepared according to Preparation Examples 1 to 5, the content of residual organic matter decreases as the heat treatment time increases, so Pt 2+ and Pt X+ It can be confirmed that it is decreasing.
[0189] (Evaluation Example 5: Elemental Analysis)
[0190] C and N elemental analysis was performed on the heterogeneous catalysts prepared in Comparative Preparation Examples 1 and 5 and Preparation Examples 1 to 7, and the analysis results are shown in Table 3 below.
[0191] In this invention, elemental analysis was performed by analyzing the gas generated by high-temperature heat treatment to calculate the content of organic elements within the catalyst.
[0192] catalyst C (wt%) N (wt%) Preparation Example 1 5.4 2.1 Preparation Example 2 4.5 1.8 Preparation Example 3 4.0 1.7 Preparation Example 4 3.8 1.5 Preparation Example 5 3.3 1.4 Preparation Example 6 1.1 3.0 Preparation Example 7 0.9 2.5 Comparative Manufacturing Example 1 0.1 0 Comparative Manufacturing Example 5 0.8 2.1
[0193] Referring to Table 3 above, it was found that the C content of the heterogeneous catalysts according to Preparation Examples 1 to 5 was 0.8 wt% to 5.4 wt%, whereas the C content of the catalyst according to Comparative Preparation Example 1 was 0.1 wt%.
[0194] In addition, the N content of the heterogeneous catalyst according to Preparation Examples 1 to 5 was found to be 1.4 wt% to 3.0 wt%.
[0196] (Evaluation Example 6: TEM-EDS Analysis)
[0197] The surface of the heterogeneous catalyst according to Preparation Example 3 was mapped by TEM (Transmission Electron Microscopy)-EDS (Energy Dispersive X-ray Spectroscopy) and is shown in Fig. 5.
[0198] Referring to Fig. 5, it can be seen that Si and Pt elements are uniformly dispersed on the surface of the prepared heterogeneous catalyst. Additionally, it can be seen that N elements are uniformly dispersed, and from this, it can be seen that PEI residues are present on the catalyst surface after surface modification.
[0200] (Experimental Example 1: Selective Chiral Synthesis under Atmospheric Pressure Conditions Using Heterogeneous Catalysts)
[0201] The heterogeneous catalysts prepared in Preparation Examples 1 to 7 and Comparative Preparation Examples 1 to 5 were loaded into a tube furnace and reduced with 5% H2 gas (balance gas was Ar) at 200 °C for 2 hours. The reduced catalyst was transferred to a three-necked flask, 5 mL of acetic acid was added, and the mixture was stirred at 150 rpm for 5 minutes. Subsequently, a solution of 2 mg of cinchonidine dispersed in 3 mL of acetic acid was injected into the three-necked flask as a chiral modifier, and a chiral catalyst was prepared by flowing hydrogen gas for 15 minutes. Next, a solution of 0.55 mmol of methyl pyruvate dispersed in 2 mL of acetic acid was added, and the synthesis reaction was carried out while stirring at 500 rpm. Here, the hydrogen pressure was set to 0.1 MPa under atmospheric pressure conditions, and the mixture was continuously stirred to allow the hydrogen to diffuse smoothly into the solution. Among the chiral compounds synthesized at this time, (R)-methyl lactate was predominantly obtained.
[0202] The synthesized chiral compounds were analyzed using gas chromatography equipped with a Chirasil-Dex CB capillary column (CP7502, 25 m × 0.25 mm × 0.25 μm, Agilent), and enantiomeric excess (ee), an indicator of enantiomer selectivity, was measured after reaching a conversion rate of 100%. ee was calculated by Equation 1 below, and the ee for each catalyst is shown in Table 4.
[0203] [Equation 1]
[0204] ee (%) = |[R]-[S]| / ([R]+[S])*100%
[0205] In the above equation, [R] and [S] represent the production amounts of the mirror-image optical isomer products, R-methyl lactate and S-methyl lactate, respectively.
[0207] catalyst Conversion Rate [%] ee [%] Preparation Example 1 100 84.9 Preparation Example 2 100 88.5 Preparation Example 3 100 90.9 Preparation Example 4 100 86.1 Preparation Example 5 100 84.9 Preparation Example 6 100 84.1 Preparation Example 7 100 81.7 Comparative Manufacturing Example 1 100 78.8 Comparative Manufacturing Example 2 Unreacted Unreacted Comparative Manufacturing Example 3 Unreacted Unreacted Comparative Manufacturing Example 4 Unreacted Unreacted Comparative Manufacturing Example 5 100 77.9
[0208] Referring to Table 4 above, it can be seen that when heterogeneous catalysts according to Comparative Preparation Examples 2 to 4 were used, the reaction did not proceed because the surface of the active metal was obscured by an excess amount of organic matter. This can be confirmed from the CO adsorption amount results in Table 1 above. Meanwhile, when heterogeneous catalysts according to Comparative Preparation Examples 1 and 5 were used, the ee was found to be 78.8% and 77.9%, respectively.
[0209] On the other hand, when using heterogeneous catalysts according to Preparation Examples 1 to 7, it can be seen that ee is 81.7% to 90.9%, which is higher than Comparative Preparation Examples 1 and 5.
[0210] Meanwhile, when using the heterogeneous catalyst according to Manufacturing Examples 1 to 5, it can be confirmed that as the heat treatment time of the heterogeneous catalyst increases, the ee tends to increase and then decrease again.
[0211] It is believed that as the heat treatment time increased, the organic material coating the surface of the platinum particles volatilized, causing the ee to increase due to the increased catalytic role of the platinum particles, and then as the heat treatment time continued to increase, the ee decreased again due to the excessive volatilization of the organic material.
[0212] Meanwhile, when using the heterogeneous catalysts according to Preparation Examples 1 to 5, the result showing a higher ee compared to Comparative Preparation Example 1 is that, as confirmed in FIG. 4, the Pt of the platinum-supported catalyst through surface modification 2+ It is believed that this is due to the increase. One of the key factors determining enantiomer selectivity is the adsorption of cinchonidin, a chiral modifier, onto the platinum surface. Due to the nitrogen contained in the modified support, electrons from platinum are transferred to nitrogen, lowering the electron density of platinum, and it is presumed that the adsorption of cinchonidin onto the surface of platinum nanoparticles proceeds more smoothly than in Comparative Preparation Example 1. Therefore, the surface modification treatment method is based on platinum (Pt) with a low catalyst surface electron density. 2+ , Pt x+ (2 <x<4))의 증가로 인해 카이랄 개질제인 신코니딘 분자가 백금 나노 입자 표면에서의 안정적 흡착이 유도되어 PEI 처리 전 촉매 대비 거울상 이성질체에 대한 선택도가 향상된 것으로 사료된다.
[0214] (Experimental Example 2: Selective Chiral Synthesis Using Regenerative Heterogeneous Catalyst)
[0215] The heterogeneous catalyst prepared in Preparation Example 3 was loaded into a tube furnace and reduced with 5% H2 gas (balance gas was Ar) at 200 °C for 2 hours. The reduced catalyst was transferred to a three-necked flask, 5 mL of acetic acid was added, and the mixture was stirred at 150 rpm for 5 minutes. Subsequently, a solution of 2 mg of cinchonidine dispersed in 3 mL of acetic acid was injected into the three-necked flask as a chiral modifier, and a chiral catalyst was prepared by flowing hydrogen gas for 15 minutes. Next, a solution of 0.55 mmol of methyl pyruvate dispersed in 2 mL of acetic acid was added, and the synthesis reaction was carried out while stirring at 500 rpm. Here, the hydrogen pressure was set to 0.1 MPa, which is an atmospheric pressure condition, and the mixture was continuously stirred to allow the hydrogen to diffuse smoothly into the solution. Among the chiral compounds synthesized at this time, (R)-methyl lactate was predominantly obtained.
[0216] For the catalyst reuse experiment, the catalyst in the reaction-completed solution was separated using a centrifuge and washed with 10 mL of acetic acid. Next, the supernatant was removed using a centrifuge, transferred back to a three-necked flask, 5 mL of acetic acid was added, and the mixture was stirred at 150 rpm for 5 minutes. Subsequently, a solution of 2 mg of cinchonidine dispersed in 3 mL of acetic acid was injected into the three-necked flask, and a chiral catalyst was prepared by flowing hydrogen gas for 15 minutes. Next, a second catalyst reuse experiment was performed by adding a solution of 0.55 mmol of methyl pyruvate dispersed in 2 mL of acetic acid and stirring at 500 rpm. The above catalyst separation and subsequent reuse reaction process was repeated 10 times for a total of 10 catalyst reuse tests, and the results of the catalytic reaction are shown in Fig. 6.
[0217] Figure 6 shows the experimental results of selective chiral synthesis according to the regeneration cycle of a heterogeneous catalyst prepared according to Preparation Example 3.
[0218] Referring to Figure 6, a negligible decrease in conversion rate of less than 5% was observed starting from the 9th catalyst reuse experiment, but it was confirmed that the high ee of approximately 90% was well maintained even during a total of 10 reuse catalyst reactions. Therefore, it can be confirmed that the high selectivity for enantiomers is well maintained even when the surface-modified heterogeneous catalyst is reused multiple times.
[0220] (Experimental Example 3: Selective Chiral Synthesis under Pressurized Conditions Using Heterogeneous Catalysts)
[0221] Chiral synthesis experiments under pressurized conditions were performed as follows using heterogeneous catalysts according to Preparation Example 3 and Comparative Preparation Example 1.
[0222] 30 mg of the sample and 5 mL of an acetic acid solution containing 2 mg of the chiral modifier cinchonidine were placed in a high-pressure vessel. A chiral catalyst was prepared by stirring at 150 rpm while flowing hydrogen gas through the solution for 15 minutes under room temperature conditions. Subsequently, the hydrogen pressure was raised to 0.5 to 5.0 MPa, and a solution of 0.55 mmol of the reactant methyl pyruvate dispersed in 2 mL of acetic acid was added, followed by stirring at 500 rpm to predominantly obtain the chiral compound (R)-methyl lactate. All procedures were performed at room temperature.
[0223] Figure 7 shows the enantiomer selectivity according to hydrogen pressure, i.e., reaction pressure.
[0224] Referring to FIG. 7, it can be seen that in the pressure range of 0.1 MPa to 5.0 MPa, the catalyst according to Preparation Example 3 exhibits a higher ee compared to the catalyst according to Comparative Preparation Example 1. Meanwhile, when using the catalyst according to Preparation Example 3, it can be seen that the highest ee value of 96.1% is observed at 1.0 MPa.
[0225] Therefore, in the case of catalysts resulting from organic surface modification, it can be confirmed that high selectivity for enantiomers is well maintained even under pressurized operating conditions.
[0227] (Experimental Example 4: Selective chiral synthesis under atmospheric pressure conditions with different chiral modifiers)
[0228] Chirals were synthesized by modifying the heterogeneous catalyst according to Preparation Example 3 and the heterogeneous catalyst according to Comparative Preparation Example 1 using different chiral modifiers.
[0229] A heterogeneous catalyst was loaded into a tube furnace and reduced at 200 °C with 5% H2 gas (balance gas was N2) for 2 hours. The reduced catalyst was transferred to a three-necked flask, 5 mL of acetic acid was added, and the mixture was stirred at 150 rpm for 5 minutes. Subsequently, a solution of 2 mg of cinchonidine dispersed in 3 mL of acetic acid was injected into the three-necked flask as a chiral modifier, and a chiral catalyst was prepared by flowing hydrogen gas for 15 minutes. Next, a solution of 0.55 mmol of methyl pyruvate dispersed in 2 mL of acetic acid was added, and the synthesis reaction was carried out while stirring at 500 rpm. Here, the hydrogen pressure was set to 0.1 MPa, which is an atmospheric pressure condition, and the mixture was continuously stirred to allow the hydrogen to diffuse smoothly into the solution. Among the chiral compounds synthesized at this time, (R)-methyl lactate was predominantly obtained.
[0230] The synthesized chiral compounds were analyzed using gas chromatography equipped with a Chirasil-Dex CB capillary column (CP7502, 25 m × 0.25 mm × 0.25 μm, Agilent), and enantiomeric excess (ee), an indicator of enantiomer selectivity, was measured after reaching a conversion rate of 100%. ee was calculated by Equation 1 above, and the ee for each catalyst is shown in Tables 5 and 6.
[0231] chiral modifiers product catalyst Conversion Rate [%] ee [%] CD (cinchonidine) (R)-methyl lactate Comparative Example 1 Pt / SiO2 100 78.8 Preparation Example 3 Pt / PEI-SiO2-3 100 90.9 CN(cinchonine) (S)-methyl lactate Comparative Example 1 Pt / SiO2 100 56.5 Preparation Example 3 Pt / PEI-SiO2-3 100 69.2 QD(quinidine) (S)-methyl lactate Comparative Example 1 Pt / SiO2 100 66.3 Preparation Example 3 Pt / PEI-SiO2-3 100 79.8 QN(quinine) (R)-methyl lactate Comparative Example 1 Pt / SiO2 100 85.4 Preparation Example 3 Pt / PEI-SiO2-3 100 90.9
[0232] reactants chiral modifiers catalyst Conversion Rate [%] ee [%] MtPy(methyl pyruvate) CD(cinchonidine) Comparative Example 1 Pt / SiO2 100 78.8 Preparation Example 3 Pt / PEI-SiO2-3 100 90.9 EtPy(ethyl pyruvate) Comparative Example 1 Pt / SiO2 100 64.9 Preparation Example 3 Pt / PEI-SiO2-3 100 76.6 EOPB (ethyl 2-oxo-4-phenylbutyrate) Comparative Example 1 Pt / SiO2 100 58.7 Preparation Example 3 Pt / PEI-SiO2-3 100 67.4 MBF(methyl benzoylformate) Comparative Example 1 Pt / SiO2 100 51.8 Preparation Example 3 Pt / PEI-SiO2-3 100 65.9
[0233] Referring to Tables 5 and 6 above, it can be confirmed that when the surface-modified catalyst of Preparation Example 3 is used, it exhibits a higher ee in all chiral modifiers than the surface-modified catalyst of Comparative Example 1, thereby showing higher enantiomer selectivity.
[0235] Although preferred embodiments of the present invention have been described above, the present invention is not limited thereto and can be implemented with various modifications within the scope of the claims, the detailed description of the invention, and the attached drawings, and it is obvious that such modifications also fall within the scope of the present invention.
[0236] Therefore, the substantive scope of the present invention shall be defined by the appended claims and their equivalents.
Claims
Claim 1 A heterogeneous catalyst for selective chiral synthesis comprising: a silica support; and metal particles supported on the silica support; wherein a polyimine-based polymer is located on the surface of the silica support, the polyimine-based polymer is polyethyleneimine, and the metal particles comprise platinum (Pt). Claim 2 delete Claim 3 delete Claim 4 A heterogeneous catalyst for selective chiral synthesis according to claim 1, wherein the dispersion of metal particles supported on the silica support is 5.0% to 25.0%. Claim 5 In claim 1, the CO adsorption amount of the heterogeneous catalyst is 0.050 cm 3 / g to 0.290 cm 3 / g, heterogeneous catalyst for selective chiral synthesis. Claim 6 A heterogeneous catalyst for selective chiral synthesis according to claim 1, wherein the average particle size (D50) of the metal particles supported on the silica support is 1.65 nm to 1.75 nm. Claim 7 A heterogeneous catalyst for selective chiral synthesis according to claim 1, wherein the size of the metal particles supported on the silica support is in the range of 1.0 nm to 2.5 nm. Claim 8 A heterogeneous catalyst for selective chiral synthesis according to claim 7, wherein, based on the total number of metal particles supported on the silica support, the percentage of metal particles with a particle size of 2.0 nm to 2.5 nm is in the range of 10% to 25%. Claim 9 A heterogeneous catalyst for selective chiral synthesis according to claim 7, wherein, based on the total number of metal particles supported on the silica support, the percentage of metal particles with a particle size of 1.0 nm to 1.5 nm is in the range of 20% to 30%. Claim 10 A heterogeneous catalyst for selective chiral synthesis according to claim 1, wherein the carbon content is in the range of 3.0 wt% to 5.5 wt% based on the total mass of the heterogeneous catalyst. Claim 11 The heterogeneous catalyst for selective chiral synthesis according to claim 1, wherein the heterogeneous catalyst has an intensity ratio P2 / P1 value of the peak (P2) appearing between 71 to 73 eV to the peak (P1) appearing between 70 to 71 eV during X-ray photoelectron spectroscopy (XPS) analysis, which is 1.21 to 4.
00. Claim 12 A method for preparing a heterogeneous catalyst for selective chiral synthesis, comprising: a step of mixing and reacting a silica support with a polyimine-based polymer to obtain a modified silica support; and a step of mixing and reacting the modified silica support with a metal salt to obtain a catalyst; wherein 150 wt% to 250 wt% of the polyamine-based polymer is mixed based on the mass of the silica support, the polyimine-based polymer is polyethyleneimine, and the metal salt comprises platinum (Pt). Claim 13 delete Claim 14 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein the step of mixing and reacting the silica support with a polyimine-based polymer to obtain a modified silica support comprises: a step of preparing a dispersion by dispersing the silica support in distilled water; a step of obtaining a mixture by mixing an aqueous solution of the polyimine-based polymer with the dispersion; and a step of heat-treating the mixture. Claim 15 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 14, the step of mixing a polyimine-based polymer into the dispersion to obtain a mixture involves stirring the mixture at a stirring speed of 400 rpm to 600 rpm. Claim 16 A method for producing a heterogeneous catalyst for selective chiral synthesis, wherein the step of heat-treating the mixture comprises: a step of heating the mixture to obtain a dried solid; and a step of calcining the dried solid to obtain a modified silica support. Claim 17 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 16, the step of heating the mixture to obtain a dried solid is performed at a temperature of 90°C to 110°C for 10 to 14 hours. Claim 18 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 16, the step of calcining the dried solid to obtain a modified silica support is performed at a temperature of 300°C to 400°C for 1 hour to 9 hours. Claim 19 A method for preparing a heterogeneous catalyst for selective chiral synthesis according to claim 12, wherein the step of obtaining a catalyst by mixing and reacting the modified silica support and a metal salt comprises: a step of obtaining a metal salt solution by dispersing the metal salt in an organic solvent; a step of obtaining a mixed dispersion by adding the modified silica support to the metal salt solution; and a step of heat-treating the mixed dispersion. Claim 20 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 19, the step of adding the modified silica support to the metal salt solution to obtain a mixed dispersion is performed by adding the modified silica support to the metal salt solution and then stirring for 10 to 14 hours at a stirring speed of 150 to 250 rpm. Claim 21 A method for producing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 19, the step of adding the modified silica support to the metal salt solution to obtain a mixed dispersion is performed at a temperature in the range of 35°C to 55°C. Claim 22 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 19, the step of heat-treating the mixed dispersion comprises: a step of heating the mixed dispersion to evaporate a solvent to obtain a catalyst precursor; and a step of calcining the catalyst precursor to obtain a catalyst. Claim 23 A method for preparing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 22, the step of heating the mixed dispersion to evaporate the solvent to obtain a catalyst precursor is heating at a temperature in the range of 70°C to 90°C. Claim 24 A method for producing a heterogeneous catalyst for selective chiral synthesis, wherein, in claim 22, the step of calcining the catalyst precursor to obtain the catalyst is to calcin at a temperature in the range of 300°C to 400°C in a reducing atmosphere. Claim 25 A method for synthesizing selective chiral, comprising: a step of mixing and pretreating a heterogeneous catalyst and a chiral modifier according to claim 1; and a step of synthesizing selective chiral by introducing an organic solution in which a chiral raw material is dissolved into the pretreated heterogeneous catalyst. Claim 26 A method for synthesizing a selective chiral according to claim 25, wherein the chiral modifier comprises one or more selected from cinchonidine, cinchonine, quinine, or quinidine. Claim 27 A method for synthesizing selective chirals according to claim 25, wherein the step of mixing and pretreating the heterogeneous catalyst and the chiral modifier comprises: a step of heat-treating the heterogeneous catalyst in a reducing atmosphere to obtain a reduced heterogeneous catalyst; a step of dispersing the reduced heterogeneous catalyst in an organic solvent and then mixing it with a chiral modifier to obtain a mixture of the heterogeneous catalyst and the chiral modifier; and a step of supplying hydrogen gas to the mixture of the heterogeneous catalyst and the chiral modifier to form a hydrogen atmosphere. Claim 28 A method for synthesizing selective chirals according to claim 27, further comprising the step of supplying hydrogen gas to a mixture of the heterogeneous catalyst and chiral reformer to form a hydrogen atmosphere, and then supplying hydrogen gas to pressurize it to a range of 0.5 MPa to 5.0 MPa. Claim 29 A method for synthesizing selective chirals according to claim 25, wherein, in the step of mixing and pretreating the heterogeneous catalyst and the chiral modifier, the heterogeneous catalyst is regenerated and used 10 or more times. Claim 30 A method for synthesizing a selective chiral according to claim 25, wherein the selective chiral is one class of chirals derived from a compound represented by the following chemical formula 1, and the selectivity is 60% or more. [Chemical Formula 1] (In Formula 1, R1 and R2 each independently comprise an unsubstituted or substituted alkyl group; an unsubstituted or substituted aryl group; and a halogen group.)
